Response of North Pacific storm tracks to multiscale SST anomalies in a stable state of the Kuroshio extension system during the cold season - Chen, Chaohui; Zhang, Jianqi; Chen, Xiangguo (Frontiers in Earth Science, 2022)
In the present study, the response of North Pacific storm tracks to spatial multiscale (large-scale and mesoscale) sea surface temperature anomalies (SSTAs) in stable state of Kuroshio Extension (KE-related SSTAs) system are investigated. The results show that storm tracks are significantly strengthened with local enhanced rainfall in the central North Pacific and near the west coast of the North American continent in response to KE-related large-scale SSTAs, while they shift to the north and are significantly strengthened in the central-eastern North Pacific and Gulf of Alaska with remote impact on precipitation along west coast of North America continent in response to KE-related mesoscale SSTAs. The anomalous storm tracks influenced by KE-related SSTAs at different spatial scales are closely related to the locations of low-level baroclinicity. The response of horizontal advection of temperature to different scales of KE-related SSTAs in the lower atmosphere plays an important role in resulting baroclinicity anomalies.